Solvation structure and dynamics of Ag+ in aqueous ammonia solutions: A molecular simulation study - Sansotta, Stefano; Zahn, Dirk (Journal of Chemical Physics, 2017)
We present an ab initio-based force-field for silver ion interactions with water and ammonia. Compared to quantum calculations, our model allows for rather large-scale molecular dynamics simulations of silver solutions of aqueous ammonia. For a series of NH3:H2O ratios ranging from 1 to 20 mol. %, Ag+ ions were mainly found as octahedral [Ag(NH3)x(H2O)]6-x+ coordination complexes with preferential values of x ranging from 0 to 3. In the first coordination structure, water łeftrightarrow ammonia exchanges occur within a 1-3 ps time scale and, depending on the NH3 concentration, imply significant fluctuations of x covering the whole range from 0 to 6. Based on ns-scale molecular dynamics simulations, chemical potentials are derived for all Ag+ coordination species as functions of temperature and ammonia concentration. Moreover, we compare the diffusion constants of the [Ag(H2O)6]+ to [Ag(H2O)3(NH3)3]+ coordination complexes, based on the solutions of the corresponding ammonia content.
EAM Import::2019-03-13